Регулювання напруги в електричних мережах у задачах надійності електропостачання та енергосбереження - Грабко, В.В.; Бальзан, І.В. (Технічна електродинаміка, 2012)
There had been suggested an approach stipulating for the creation of the voltage regulation system using the power transformer with the device for regulation under loading of the regional substation in connection with the transformers of the final substation in the electric net which submit the information on voltage value to the voltage regulator of the regional substation via transmission channel. The voltage quality on the consumers busses as well as the reliability of the device for regulation under loading are being improved due to the reduction in number of switching. The electric energy losses in the transformers of the final substations are also reduced at the cost of maintaining the value of the voltage on their busses within the permissible limits. There had been suggested the law of voltage regulation which realizes this approach.